Analysis of Mistakes in Indonesian Language in The Community of Mekar Tanjung Village, Teluk Dalam District - Dailami, Dailami; Heni Subagiharti; Sri Rahmayanti; Hanifah Sitorus Pane (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The purpose of this study is to determine the style of language and describe the meaning of Fiersa Besari's songs through a Hermeneutic approach based on the theory of Frierdrich Ernst Daniel Schleirmacher with the theory of Grammatical Interpretation and Psychological Interpretation. This type of research method is descriptive qualitative. Data collection methods and techniques used in this study, namely library methods and field methods where the techniques used are recording techniques, listening techniques and note taking techniques. The data analysis technique focuses on how hermeneutics works in discussing the interpretation of meaning. The results of this study the author concludes that the lyrics of the song Fiersa Besari uses a variety of language styles such as metonymy, hyperbole, pleonasm, personification, metaphor, sarcasm, eroticism, assonation, polysindenton, epithet, satire, cynicism, and irony . The meanings contained in the lyrics of the song are: (1) about a long distance love story, (2) a devotional song to improve attitudes towards the Indonesian homeland, (3) an unrequited love story, (4) satire to the people and the Indonesian government. Language is associated with the identity of a nation. Communication is difficult between ethnic groups because the use of Indonesian orally is influenced by the dialect of each ethnic group. This study aims to determine errors in spoken Indonesian among the people of Mekar Tanjung Village, Teluk Dalam District in terms of phonological, morphological and syntactic interference. Qualitative research methods, data analysis techniques using interviews with three different sources. The results of the study explained that errors in spoken language in the aspect of phonological interference were found in 13 words, errors in spoken language in the aspect of morphological interference were found in 11 (four) words and errors in spoken language in the community of Mekar Tanjung Village, Teluk Dalam District in terms of syntactic interference aspects were found as many as 11 (eleven) phrases, 5 (five) sentences of errors in clauses and 10 (ten) sentences in sentences without a subject.